Pengembangan Media Pembelajaran Berbasis Augmented Reality (AR) Pada Materi Momentum Kelas XI - Bachtiar, Bachtiar; Darsikin, Darsikin; N. Laratu, Wahyuni (JPFT (Jurnal Pendidikan Fisika Tadulako Online), 2024)
This study aims to develop and determine the validity and feasibility of Augmented Reality (AR)-based learning media in physics subjects. This study is a development research or Research & Development (R&D) using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluate). The subjects of the study were 30 students of class XI-5 SMAN 7 Palu in the 2022/2023 academic year. The instrument used was a closed questionnaire with a Likert scale type. Based on the results of the assessment by material experts on AR-based learning media, the category was "valid", the assessment from design experts obtained the category "valid", and based on the results of the student response questionnaire, the category was "very good".